2018
DOI: 10.1080/00365521.2018.1486882
|View full text |Cite
|
Sign up to set email alerts
|

Success and safety of high infliximab trough levels in inflammatory bowel disease

Abstract: High infliximab trough levels provide better control of inflammation in inflammatory bowel disease without increasing the risk of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…However, where infection risk has been compared to actual infliximab concentrations, no such relationship has been observed in retrospective studies. No increased risk of infection was observed in 183 patients with infliximab trough levels >7 µg/mL and in 180 patients >15 µg/mL . Somewhat counterintuitively in the latter study, higher infectious complications were actually observed in the group with an infliximab level less than 15 µg/mL (33% vs 19% P = 0.04).…”
Section: Determination Of the Therapeutic Range For Anti‐tnf Agentsmentioning
confidence: 61%
“…However, where infection risk has been compared to actual infliximab concentrations, no such relationship has been observed in retrospective studies. No increased risk of infection was observed in 183 patients with infliximab trough levels >7 µg/mL and in 180 patients >15 µg/mL . Somewhat counterintuitively in the latter study, higher infectious complications were actually observed in the group with an infliximab level less than 15 µg/mL (33% vs 19% P = 0.04).…”
Section: Determination Of the Therapeutic Range For Anti‐tnf Agentsmentioning
confidence: 61%
“…Because of the known mismatch between serum and tissue anti‐TNF levels, especially in patients with active disease, we hypothesize that targeting a higher serum trough level above the 7.0 μg/mL upper limit of the therapeutic window might better neutralize tissue TNF and hence increase mucosal healing rates, especially in patients with a high mucosal IL13RA2 expression. Retrospective data already suggested that higher trough levels are safe and result in better endoscopic outcomes . Similarly, recent prospective data from the UK PANTS study also demonstrated the beneficial impact of higher post‐induction serum levels on 1‐year outcome in anti‐TNF‐treated patients .…”
Section: Discussionmentioning
confidence: 89%
“…These patients typically have low infliximab trough levels, suggesting a pharmacokinetic issue . Conversely, high trough levels have been associated with clinical and biochemical remission, C‐reactive protein and faecal calprotectin normalisation, mucosal healing and even fistula healing . Consequently, different strategies have been developed to tackle low trough levels, such as adding azathioprine to infliximab during the most vulnerable period of 6‐12 months after its initiation, a strategy known as combination treatment .…”
Section: Introductionmentioning
confidence: 99%
“…By improving pharmacokinetics, azathioprine co‐treatment increases infliximab trough levels . Alternatively, trough levels can also be increased by escalating the dose of infliximab or by shortening the interval between infusions of infliximab—a strategy known as “optimised infliximab monotherapy.” The latter may have the advantage of increased safety, as high trough levels were not associated with an increased risk of complications . Conversely, combination treatment has a well‐documented increased risk of infection and malignancy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation